Pengaruh Teknik Penyimpanan Terhadap Mutu Pakcoy (Brassica rapa L) Serta Konsentrasi Pakcoy Terhadap Sifat Fisik Dan Sensoris Jus Panas (Pakcoy Nanas) - Fitria Ari Murti; Hesti Nur’aini (Universitas Dehasen Bengkulu, 2023)
Horticultural commodities are still active in carrying out their metabolic activities after being harvested. Pakcoy vegetables easily experience quality deterioration or damage (perishable) which causes their shelf life to not last long (2-4 days). The purpose of this study was to evaluate the effect of storage techniques on the quality of pakcoy vegetables and the effect of pakcoy concentration on the physical and sensory properties of hot juice (pakchoy pineapple). The research was carried out through experiments consisting of two studies, namely evaluating the effect of storage techniques on the quality of pakcoy vegetables and evaluating the effect of concentration of pakcoy on the sensory quality of hot juice (pineapple pakcoy). The best pakcoy storage technique can be done by using wrap or polypropylene packaging, without removing the roots. The higher the concentration of pakcoy, the higher the TPT of hot juice. A significant difference occurred at a concentration of 20%. Sensory-wise, hot juice with 20% pakcoy concentration was the most preferred, with a color score of 3.7 (like), taste 3.7 (like), aroma 3.6 (like) and texture 3.3 (neutral).